EVALUASI TATA KELOLA IT DAN PREDIKSI KINERJA BISNIS BERBASIS DATA SCIENCE UNTUK OPTIMALISASI STRATEGI PADA MANAJEMEN HOTEL DAILY INN - Irsyad, Muhammad; Siahaan, Andysah Putera Utama; Marlina, Leni (Smart Education, 2025)
Abstract: This study aims to evaluate the maturity level of Information Technology (IT) governance at Hotel Daily Inn using the COBIT 2019 framework and to predict hotel reservation trends through a data science approach using the Bayesian Structural Time Series (BSTS) algorithm. A mixed-method approach is applied, combining qualitative methods for IT governance evaluation and quantitative methods for reservation prediction. Data collection involves literature review, interviews with four main divisions (Front Office, Food & Beverage, Housekeeping, and Security), observations, and documentation of reservation data from 2018 to 2022. The evaluation results indicate that the IT governance maturity level is at the